The effect of composition and shape variations on compressive strength slag depressant - Bening Nurul Hidayah Kambuna; Soesaptri Oediyani; Della Izzaty Salman; Kusnadi Kusnadi (Jurnal Teknika, 2021)
The steel-making process begins with a reduction process carried out in a blast furnace (BF) then continues with the refining process in the converter. In the refining process, there is a slag foam formed from the reaction of oxygen with hot metal. An additive called a slag depressant is needed to reduce foam formation in the slag. Slag depressants are made using paper mill waste, limestone, and slag blast furnaces. This study aims to increase the compressive strength of the slag depressant by varying the composition and shape variations. Variations in the composition used were with and without the addition of BF slag, while variations in the shapes used were cylinder, round, and cube. Making slag depressants begins with the stages of mixing, compacting, and drying. Slag depressant drying is carried out in the sun for ± eight days. The slag depressant raw material was analyzed using the XRF method to see the chemical composition of the raw material. The resulting slag depressant was then analyzed for proximate analysis, compression test, drop test, and porosity test. In this study, the best quality slag depressant with high compressive strength and low porosity values is the slag depressant in a cylindrical shape, and the ratio of paper waste to limestone is 80:20%. The resulting compressive strength value is 1207.5 N/cm2 and has a porosity of 34.7%. The addition of BF slag in this study was proven to affect the compressive strength of the slag depressant. The highest compressive strength value was achieved by adding 10% slag blast furnace to 10%, which was 862.08 N/cm2. Proses pembuatan baja diawali dengan proses reduksi yang dilakukan dalam blast furnace (BF) kemudian dilanjutkan dengan proses pemurnian dalam converter. Dalam proses pemurnian, terdapat gelembung/busa slag (slag foam) yang terbentuk dari reaksi oksigen dengan hot metal. Untuk mengurangi pembentukan busa pada slag maka diperlukan bahan aditif yang disebut dengan slag depressant. Slag depressant dibuat dengan menggunakan limbah pabrik kertas, batu kapur dan slag blast furnace. Penelitian ini bertujuan untuk meningkatkan kekuatan tekan slag depressant dengan melakukan variasi komposisi dan variasi bentuk. Variasi komposisi yang digunakan yaitu dengan dan tanpa penambahan slag BF sedangkan variasi bentuk yang digunakan yaitu silinder, bulat dan kubus. Proses pembuatan slag depressant diawali dengan tahapan mixing, kompaksi dan pengeringan. Pengeringan slag depressant dilakukan di bawah sinar matahari ±8 hari. Bahan baku slag depressant dianalisis dengan metode XRF untuk melihat komposisi kimia bahan baku tersebut. Slag depressant yang dihasilkan kemudian dilakukan analisis proksimat, uji tekan, uji jatuh dan uji porositas. Pada penelitian ini didapatkan slag depressant dengan kualitas paling baik dengan nilai kuat tekan tinggi dan porositas rendah yaitu pada slag depressant bentuk silinder dan perbandingan limbah kertas dengan batu kapur sebesar 80: 20 %. Nilai kuat tekan yang dihasilkan sebesar 1207,5 N/cm2 dan porositas sebesar 34,7%. Penambahan slag BF dalam penelitian ini terbukti mempengaruhi kuat tekan slag depressant. Nilai kuat tekan tertinggi dicapai pada penambahan 10% slag blast furnace 10% yaitu sebesar 862,08 N/cm2.